A case of congenital tufted angioma - Pingxiu HE; Lifang CHENG; Yi WU; Bixia XIA (Pifu-xingbing zhenliaoxue zazhi, 2023)
A case of congenital tufted angioma is reported. A 5-year-old boy presented with a dark red plaque on the right shoulder blade for 5 years. The dermatological examination showed a smooth dark-red patch of 5.0 cm×4.0 cm in size on the right shoulder blade, with raised broders and a sunken center (4 mm deep). Histopathological examination showed lots of tumor masses composed of capillaries and cannonballs of spindle or oval endothelial cells without atypia in the dermis. Immunohistochemistry showed positive for CD31, CD34, and <1% of Ki-67 positive. The diagnosis was congenital tufted angioma. The lesion was completely excised and no recurrence was observed during the one and a half-year follow-up.